ANALISIS DANA PIHAK KETIGA, KECUKUPAN MODAL, DAN RISIKO KREDIT TERHADAP PENYALURAN KREDIT PADA BANK UMUM - Arrisa Diana Kartika Siregar, - (2019)
This research is a quantitative research which aims to determine the effect of Third Party Funds, Capital Adequacy and Credit Risk on Credit Distribution. The population used in this study is the National Commercial Bank, which numbered 41 companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2017. By using purposive sampling method, there are 27 banks as research samples. The type of data used is secondary data. Testing the hypothesis in this study uses panel data regression analysis with program Eviews 9.0 and a significant level of 0.05. The results of this study indicate that Third Party Funds have a positive and significant effect on Credit Distribution, while Capital Adequacy as measured by the Capital Adequacy Ratio (CAR) and Credit Risk as measured by Non Performance Loans (NPL) does not affect Banking Credit Distribution.